Analysis and improvement of a novel image fusion encryption algorithm based on DNA sequence operation and hyper-chaotic system - Ozkaynak, Fatih; Yavuz, Sirma (Springer, 2014)
Recently, a novel image encryption algorithm based on DNA operation and hyper-chaotic system has been proposed by Zhang et al. The encryption algorithm first shuffles the image pixels using Chen chaotic system. After shuffling process, the proposed encryption algorithm changes the gray levels of the image pixels using DNA operation. In this study, we give out complete break for the proposed cryptosystem using a chosen plaintext attack. Both mathematical proofs and experimental results are presented to support the proposed attacks. Main motivation behind this study was to analyze whether proposed image encryption algorithm is suitable for secure communication or not. Based on the results of our analysis, we also discussed the potential improvements for the algorithm and proposed a modified new encryption algorithm accordingly. Essential elements of designing secure image encryption algorithms and potential application areas are also stated.
Keywords: Chaos; Cryptography; Cryptanalysis; Image encryption; DNA operation